Business Plan : Khaafé Sdn Bhd / Wan Ahmad Afiq Wan Ab Aziz …[et al.] - Wan Ab Aziz, Wan Ahmad Afiq; Abdul Salam, Nur Hadirah; Hashim, Nur Hasmira; Ramlee, Nur Farhana; Mohd Kamsol, Nurul Khalis; Mat Nawi, Nur Anisya (2021)
KHAAFÉ Sdn Bhd. is a new company which provide a high quality of food and beverage services to the customer. KHAAFÉ Sdn Bhd. consists of six partnership business which hold important positions in the company such as General Manager, Administrative Manager, Marketing Manager, Operational Manager, Human Resource Manager and Financial Manager. Each of member contribute same amount of capital which it is RM 10,000 and the rest are RM 100,000 is from Maybank’s loan. Six of us will hold different responsibilities in order to improve our business to be better in the future. After our long-term research and observation, we had decided to commence this business because we want to do something different which is more unique than the existing eateries in terms of services, design and most importantly the menu and food prices. KHAAFÉ Sdn Bhd. is a company which focuses on food and beverages production in Malaysia. Actually, the word Khaafé is the combination of our six partners name while tagline “Sweet Bitterness until The Last Drop” is a special word chosen by our financial manager Wan Ahmad Afiq. Our unique café is located at strategic place, main centre or attraction place for local people and tourists. To make our business more attractive and unique from the others, we have decided to inject some innovation in our customer service, design and the menu itself. For customer service, our café will be provided with a variety of option for customer to purchase their orders through web site and physical method. There will be also an option for customer to choose the riders for delivering their orders straight away until their place. Even though there are lots of café and restaurant out there but it’s rarely for us to find one cafe that serves 1 Malaysian dishes. KHAAFÉ Sdn Bhd. is the one and only that make some innovation with serves special dishes which it is traditional food for every race in Malaysia with special ingredients such as collagen and vitamins. As we know, Malaysia is country that have a variety of races, ethnic, background, therefore, we want to use food as our weapon to unite and create some happiness and also harmonious among Malaysian. Peace and harmony are important element that every country must preserved in order to protect our own country.